2019
DOI: 10.3389/fphys.2019.01144
|View full text |Cite
|
Sign up to set email alerts
|

Cullin Ring Ubiquitin Ligases (CRLs) in Cancer: Responses to Ionizing Radiation (IR) Treatment

Abstract: Treatment with ionizing radiation (IR) remains the cornerstone of therapy for multiple cancer types, including disseminated and aggressive diseases in the palliative setting. Radiotherapy efficacy could be improved in combination with drugs that regulate the ubiquitin-proteasome system (UPS), many of which are currently being tested in clinical trials. The UPS operates through the covalent attachment of ATP-activated ubiquitin molecules onto substrates following the transfer of ubiquitin from an E1, to an E2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 190 publications
(211 reference statements)
1
43
0
1
Order By: Relevance
“…Ubiquitination is a post-translational modification of proteins, carried out by the sequential activity of a group of ligases, including ubiquitin-activating (E1), ubiquitin-conjugating (E2), and ubiquitin-ligating (E3) enzymes, on the specific lysine residues of the target substrates [ 114 ]. The human genome encodes two E1, ~35 E2, and >700 E3 ubiquitin ligases [ 115 ] and ubiquitination is primarily known for the degradation of protein substrates upon the modification. However, in recent years, this post-translational modification has emerged as a critical mechanism by which it appears to regulate diverse biological processes, including various aspects of immune function and signaling pathways [ 116 , 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ubiquitination is a post-translational modification of proteins, carried out by the sequential activity of a group of ligases, including ubiquitin-activating (E1), ubiquitin-conjugating (E2), and ubiquitin-ligating (E3) enzymes, on the specific lysine residues of the target substrates [ 114 ]. The human genome encodes two E1, ~35 E2, and >700 E3 ubiquitin ligases [ 115 ] and ubiquitination is primarily known for the degradation of protein substrates upon the modification. However, in recent years, this post-translational modification has emerged as a critical mechanism by which it appears to regulate diverse biological processes, including various aspects of immune function and signaling pathways [ 116 , 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…A 2012 study exploring coevolution of PTM sites within proteins showed that ubiquitination sites frequently coevolve with phosphorylation and acetylation sites [ 39 ]. For example, phosphorylation of protein such as cyclins during the cell cycle recruits cullin-RING E3 ligases, leading to cyclin degradation by the proteasome [ 40 ]. However, this analysis only employed 600 ubiquitination sites, so new investigations with deeper ubiquitome data may show new trends.…”
Section: Lessons From Ubiquitin Site Profilingmentioning
confidence: 99%
“…As mention previously, MLN4924 can impact the function of the CRL sub-family of E3 ligases. CRLs play a critical role in NFκB activation [ 147 ]. The SCF E3 ligase complex containing CUL1 is the most well characterized to date.…”
Section: Targeting the Ubiquitin System To Inhibit Nfκb Signallingmentioning
confidence: 99%